2005
DOI: 10.1093/molbev/msj042
|View full text |Cite
|
Sign up to set email alerts
|

Genome Plasticity and ori-ter Rebalancing in Salmonella typhi

Abstract: Genome plasticity resulting from frequent rearrangement of the bacterial genome is a fascinating but poorly understood phenomenon. First reported in Salmonella typhi, it has been observed only in a small number of Salmonella serovars, although the over 2,500 known Salmonella serovars are all very closely related. To gain insights into this phenomenon and elucidate its roles in bacterial evolution, especially those involved in the formation of particular pathogens, we systematically analyzed the genomes of 127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…A duplication that introduced a replichore imbalance of 23°did have a growth defect, but whether the defect is from replichore imbalance or the gene content of the duplication could not be distinguished. This study suggests that the disruption of replichore balance by acquisition of horizontally transferred genes is not the cause of chromosome rearrangements in host-specific S. enterica serovars as hypothesized (12)(13)(14).…”
mentioning
confidence: 75%
“…A duplication that introduced a replichore imbalance of 23°did have a growth defect, but whether the defect is from replichore imbalance or the gene content of the duplication could not be distinguished. This study suggests that the disruption of replichore balance by acquisition of horizontally transferred genes is not the cause of chromosome rearrangements in host-specific S. enterica serovars as hypothesized (12)(13)(14).…”
mentioning
confidence: 75%
“…The host with translocated genes might be able to adapt to a new niche faster than if it depended solely on substitution. Indeed, it has been shown that large-scale genome rearrangements, such as gene inversion and gene translocation, alter gene expression (Brinig et al 2006) and might play roles in niche adaptation (Colson et al 2004;Kuwahara et al 2004;Burgetz et al 2006;Coleman et al 2006;Liu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two hypotheses have previously been suggested to explain selection for locally high rearrangement frequencies. The adopt-adapt model suggests that the insertion of phages and/or GEIs leads to an unbalancing of the genome and thereby to fixation of chromosomal rearrangements, as observed in Salmonella enterica (46,47). According to the adoptadapt hypothesis, rearrangements occur until the chromosome is partitioned equally on both sides of ori and ter.…”
Section: Discussionmentioning
confidence: 99%